Simple basal meningitis in children - Reid, James Martin (The University of Edinburgh, 1903)
Simple Basal Meningitis defines itself as regards its position, though it might be more correct to describe it, as is sometimes done, as Posterior Basic Meningitis, for it is invariably met with at the posterior part of the bases of the brain, at the junction of the cerebellum with the medulla, and in the interpeduncular space. It is named "simple" in contra distinction to the tuberculous variety also affecting the base of the brain.

In this thesis, I have included only cases which have been proved either by bacteriological examination to be due to the diplococcus of Still, or where from a clinical evidence, one may conclude that such was the cause. Pneumo- coccal and meningitis secondary to suppurating conditions, I have not included. The cases to be tabulated later have all been culled from the records of the Royal Hospital for Sick Children, Edinburgh, and comprise those that were admitted to that hospital during the years 1900, 1901 and 1902.